The governance-risk scoreboard - Rodolfo Apreda (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2013)
In this paper, we set forth a scoreboard for dealing with those risks that arise from the governance of any organization. Firstly, we introduce the subject of governance risks and, secondly, we move on to a cardinal index that not only measures up governance performance but also provides with a rate of governance risks. Next, we argue for protocol that builds up a staff unit to be held accountable for the management of such risks. Afterwards, the main components of the scoreboard are disclosed: on the one side, a governance-risk toolkit and, on the other side, policy-making guidelines, whose intertwining brings about a clinical approach to governance and the Governance-Risk staff unit report to the Board of Directors. Last of all, it is shown how to put the Scoreboard into practice.
Keywords: G30; G32; G34; 330; corporate governance; governance risks; governance scoreboard; clinical approach; compliance; incremental cash-flow model; governance index